The Influence of Celebrity Endorser Toward Emotional Attachment and Brand Trust That Impact to Purchase Intention - Ursula Natalia; Mohamad Rizan; Rahmi (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2021)
The purpose of this study is to determine the influence of celebrity endorser on purchase intention with emotional attachment and brand trust as an intervention. This study uses a survey method as a data technique using a questionnaire that is distributed by online. The sample used in this study are 210 women who had never used ESQA Cosmetics in Jabodetabek. This study is using a purposive sampling technique. The SEM (Structural Equation Model) method that will be used in this research is using data processing tools, namely SPSS version 24 and Lisrel. The findings indicates that 1) celebrity endorser has a positive and significant influence on emotional attachment, 2) celebrity endorser has a positive and significant influence on consumer purchase intentions, 3) emotional attachment has a positive and significant influence on consumer purchase intentions, 4) brand trust has a positive and significant influence on consumer purchase intentions, 5) celebrity endorser has a positive and significant influence on consumer purchase intentions. Keywords : Celebrity Endorser, Emotional Attachment, Brand Trust, Purchase Intention, ESQA Cosmetics.